200 Mpc Sized Structure in the 2dF QSO Redshift Survey - Miller, L; Croom, S; Boyle, B; Loaring, N; Smith, R; Shanks, T; Outram, P (2004)
The completed 2dF QSO Redshift (2QZ) Survey has been used to search for extreme large-scale cosmological structure (around 200 Mpc) over the redshift range 0<z<2.5. and="" background.="" comoving="" correspond="" cosmic="" cosmological="" demonstrate="" detected="" detection="" do="" exist="" fluctuations="" fractional="" hence="" however,="" in="" microwave="" of="" on="" overdensities="" presently="" represent="" scales="" significant="" statistically="" that="" the="" those="" to="" underdensities="" we="">100Mpc are in the linear or only weakly non-linear regime and do not represent collapsed non-linear structures. We compare the measurements with the expectation of a standard LCDM model by measuring the variance of counts in cells and find that, provided the distribution of QSOs on large scales exhibits a mild bias with respect to the distribution of dark matter, the observed fluctuations are found to be in good agreement with the model. There is no evidence on such scales for any extreme structures that might require, for example, departures from the assumption of Gaussian initial perturbations. Thus the power-spectrum derived from the 2QZ Survey appears to provide a complete description of the distribution of QSOs. The amount of bias and its redshift dependence that is required is consistent with that found from studying the clustering of 2QZ QSOs on 10 Mpc scales, and may be adequately described by an approximately redshift-invariant power spectrum with normalisation sigma_8=1.0 corresponding to a bias at z=0 of b=1.1 rising to b=2 at the survey's mean redshift z=1.5.</z<2.5.>